ІНФЛЯЦІЯ: СУТНІСТЬ, ВИДИ ТА ШЛЯХИ ПОДОЛАННЯ - Крістіна Олегівна Яцко (International Journal of Innovative Technologies in Economy, 2018)
The strengthening of inflationary trends in the economy and the significant consequences and problems of further development of the state identified the subject of this study. The purpose of the work is to find out the causes of inflationary processes and ways to overcome them.